2014
DOI: 10.4269/ajtmh.13-0255
|View full text |Cite
|
Sign up to set email alerts
|

Wound Care in Buruli Ulcer Disease in Ghana and Benin

Abstract: Buruli ulcer (BU) is a disease affecting the skin, subcutaneous fat, and bone tissues. Wound care is important in the prevention of disabilities. Awareness of current wound care practices in BU-endemic regions is necessary for future wound care interventions. Thirty-one health care workers in Ghana and Benin were interviewed with a semi-structured interview, complemented by structural observations. Quantitative data were analyzed through t tests and one-way analysis of variance, and qualitative data through de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…6,7 A recent survey of BU wound care practices in Ghana and Benin found that gauze was the only dressing type that was used. 8 Though substantially cheaper, gauze has several disadvantages over more modern dressings, as it adheres to the wound bed and disturbs dermal regeneration upon removal causing pain during wound dressing. 9,10 In addition, it does not create a moist environment and cannot remain on the wound for more than 1 day, which for many BU patients means a daily loss of productivity of several hours (including walking to the health-care center, waiting) that can be devastating to the household economy.…”
mentioning
confidence: 99%
“…6,7 A recent survey of BU wound care practices in Ghana and Benin found that gauze was the only dressing type that was used. 8 Though substantially cheaper, gauze has several disadvantages over more modern dressings, as it adheres to the wound bed and disturbs dermal regeneration upon removal causing pain during wound dressing. 9,10 In addition, it does not create a moist environment and cannot remain on the wound for more than 1 day, which for many BU patients means a daily loss of productivity of several hours (including walking to the health-care center, waiting) that can be devastating to the household economy.…”
mentioning
confidence: 99%
“…Furthermore, lack of knowledge of BUD and thus wrong diagnosis on the part of healthcare personnel make them treat all ulcers alike. Nurses in the dressing room for example, make use of materials like normal saline, honey, purit, uzol lotion, hydrogen peroxide and savlon [16] in treating wounds. These might be successful in treating other wounds but not Buruli ulcer which can only respond to antibiotic combination therapy administered over a period of eight weeks [14,15] and 2).…”
Section: Discussionmentioning
confidence: 99%
“…As ulcerative disease forms the majority of lesions in many treatment centers, [7][8][9]12 wound care plays a pivotal role in the care and treatment outcomes of patients. 13 In addition, as a result of late presentation to health facilities, scarring and contractures may complicate the healing process, particularly among patients who are not treated early, leading to long-term functional disability and occasionally amputation of affected limbs. 1,14 In this article, we review the current knowledge on BU with particular emphasis on wound care and rehabilitation.…”
mentioning
confidence: 99%
“…The use of traditional gauze dressings has been associated with significantly higher infection rates compared to moistretentive dressings in wounds of various origins, but this has not been investigated in BU. 13 Modern dressing materials such as hydrocolloids may decrease time to healing and improve patient comfort, [81][82][83] but again there are no published data relating to their use in BU. The frequency of dressing change depends on the amount of exudate, but routinely it is daily for BU.…”
mentioning
confidence: 99%
See 1 more Smart Citation